Hepatic osteodystrophy: An important matter for consideration in chronic liver disease - López-Larramona, Germán (Baishideng Publishing Group Co., Limited, 2011)
Hepatic osteodystrophy (HO) is the generic term defining the group of alterations in bone mineral metabolism found in patients with chronic liver disease. This paper is a global review of HO and its main pathophysiological, epidemiological and therapeutic aspects. Studies examining the most relevant information concerning the prevalence, etiological factors, diagnostic and therapeutic aspects involved in HO were identified by a systematic literature search of the PubMed database. HO generically defines overall alterations in bone mineral density (BMD) (osteoporosis or osteopenia) which appear as a possible complication of chronic liver disease. The origin of HO is multifactorial and its etiology and severity vary in accordance with the underlying liver disease. Its exact prevalence is unknown, but different studies estimate that it could affect from 20% to 50% of patients. The reported mean prevalence of osteoporosis ranges from 13%-60% in chronic cholestasis to 20% in chronic viral hepatitis and 55% in viral cirrhosis. Alcoholic liver disease is not always related to osteopenia. HO has been commonly studied in chronic cholestatic disease (primary biliary cirrhosis and primary sclerosing cholangitis). Several risk factors and pathogenic mechanisms have been associated with the loss of BMD in patients with chronic liver disease. However, little information has been discovered in relationship to most of these mechanisms. Screening for osteopenia and osteoporosis is recommended in advanced chronic liver disease. There is a lack of randomized studies assessing specific management for HO.